Entrepreneurship Courses on Gamification Strategies - Nisaul Barokati Seliro Wangi; M. Hafidh Nashrullah (EDUTEC : Journal of Education And Technology, 2018)
In the learning process, the gamification strategy plays an important role in determining the achievement of learning objectives. Learning objectives will be achieved if students are able to engage in active communication both with their peers, facilitators, and with other learning resources. Characteristics of entrepreneurship courses include understanding and appreciation of entrepreneurship, the role of entrepreneurial mental attitude for self-improvement and institutions with core entrepreneurial spirit and entrepreneurial mental attitude through the introduction of entrepreneurial characteristics, growing business interest and tips on successful entrepreneurs, making business plans and making business plans. The aim of entrepreneurship courses is to provide students with an understanding and appreciation of entrepreneurship that is increasingly felt important in the face of globalization. Gamification and entrepreneurship Having several links (1) gamification strategies can provide choices and control to students when making a plant business project, (2) gamification strategies can foster confidence in their ability to face and solve challenges, (3) gamification strategies provide material and key answers to entrepreneurship courses, (4) give appreciation for the additional learning taken, and (5) help students establish social interaction through leadership activities or other social interactions. This development research seeks to design a gamification strategy in entrepreneurship courses in the Indonesian Language and Literature Study Program, FKIP UNISDA Lamongan. The Gamification Strategy developed has four basic game components, namely the rules of gamification, feedback (leaderboards, prizes, and medals), goals, and challenges. This research includes the type of development research that uses the Lee and Owl model with the following stages, (1) analyzing needs, (2) pre-test and post-test analysis, (3) design, (4) development, (5) implementation, (6) evaluation. Results of developing a gamification strategy package (1) gamification strategy (2) Lecturer guidance (3) student guide (4) Entrepreneurship book.